Politics, Culture, and the Irish American Press : 1784-1963 - Broersma, Marcel Jeroen, 1973-; O'Brien, Mark, 1973-; Reddin van Tuyll, Debra (Book collections on Project MUSE., 2020)
"This book examines the emergence of the Irish-American diaspora press and its contribution to the political and cultural lives of Irish-Americans over the course of the last two centuries"--